Sorting nexin 9 recruits clathrin heavy chain to the mitotic spindle for chromosome alignment and segregation. - Maggie P C Ma; Phillip J Robinson; Megan Chircop (PLoS ONE, 2013)
Sorting nexin 9 (SNX9) and clathrin heavy chain (CHC) each have roles in mitosis during metaphase. Since the two proteins directly interact for their other cellular function in endocytosis we investigated whether they also interact for metaphase and operate on the same pathway. We report that SNX9 and CHC functionally interact during metaphase in a specific molecular pathway that contributes to stabilization of mitotic spindle kinetochore (K)-fibres for chromosome alignment and segregation. This function is independent of their endocytic role. SNX9 residues in the clathrin-binding low complexity domain are required for CHC association and for targeting both CHC and transforming acidic coiled-coil protein 3 (TACC3) to the mitotic spindle. Mutation of these sites to serine increases the metaphase plate width, indicating inefficient chromosome congression. Therefore SNX9 and CHC function in the same molecular pathway for chromosome alignment and segregation, which is dependent on their direct association.